Cannabidiol exhibits potent anti-cancer activity against gemcitabine-resistant cholangiocarcinoma via ER-stress induction in vitro and in vivo - Thatsanapong Pongking; Phonpilas Thongpon; Kitti Intuyod; Sirinapha Klungsaeng; Raynoo Thanan; Apisit Chaidee; Naruechar Charoenram; Suppakrit Kongsintaweesuk; Chadamas Sakonsinsiri; Kulthida Vaeteewoottacharn; Somchai Pinlaor; Porntip Pinlaor (BMC, 2024)
Abstract Background Failure of treatment with gemcitabine in most cholangiocarcinoma (CCA) patients is due to drug resistance. The therapeutic potential of natural plant secondary compounds with minimal toxicity, such as cannabidiol (CBD), is a promising line of investigation in gemcitabine-resistant CCA. We aim to investigate the effects of CBD on gemcitabine-resistant CCA (KKU-213BGemR) cells in vitro and in vivo. Materials In vitro, cell proliferation, colony formation, apoptosis and cell cycle arrest were assessed using MTT assay, clonogenicity assay and flow cytometry. The effect of CBD on ROS production was evaluated using the DCFH-DA fluorescent probe. The mechanism exerted by CBD on ER stress-associated apoptosis was investigated by western blot analysis. A gemcitabine-resistant CCA xenograft model was also used and the expression of PCNA and CHOP were evaluated by immunohistochemical analysis. Results The IC50 values of CBD for KKU-213BGemR cells ranged from 19.66 to 21.05 µM. For a non-cancerous immortalized fibroblast cell line, relevant values were 18.29 to 19.21 µM. CBD suppressed colony formation by KKU-213BGemR cells in a dose-dependent manner in the range of 10 to 30 µM. CBD at 30 µM significantly increased apoptosis at early (16.37%) ( P = 0.0024) and late (1.8%) stages (P < 0.0001), for a total of 18.17% apoptosis (P = 0.0017), in part by increasing ROS production (P < 0.0001). Multiphase cell cycle arrest significantly increased at G0/G1 with CBD 10 and 20 µM (P = 0.004 and P = 0.017), and at G2/M with CBD 30 µM (P = 0.005). CBD treatment resulted in increased expression of ER stress-associated apoptosis proteins, including p-PERK, BiP, ATF4, CHOP, BAX, and cytochrome c. In xenografted mouse, CBD significantly suppressed tumors at 10 and 40 mg/kg·Bw (P = 0.0007 and P = 0.0278, respectively), which was supported by an increase in CHOP, but a decrease in PCNA expression in tumor tissues (P < 0.0001). Conclusion The results suggest that CBD exhibits potent anti-cancer activity against gemcitabine-resistant CCA in vitro and in vivo, in part via ER stress-mediated mechanisms. These results indicate that clinical explorative use of CBD on gemcitabine-resistant CCA patients is warranted.